Male and female wage functions : a quantile regression analysis using LEED and LFS portuguese databases - Figueiredo, Maria da Conceição (2015)
This paper was presented at the 3rd Linked Employer-Employee Data Workshop LEED 2013, June 27-28, Lisbon, Portugal